Analisis Strategi Pemasaran Produk Hasanah Card pada Bank Syariah Indonesia (BSI) KC Padangsidimpuan - Dinda Pradina Nasution (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
The Hasanah Card product is one of the products owned by Bank Syariah Indonesia (BSI). Hasanah Card products use mudharabah and musyarakah contracts, namely obtaining profit sharing. However, as the sharia banking sector in Indonesia continues to develop, marketing strategies are needed to face competition, especially in financing products. Marketing is carried out in order to fulfill people's needs and desires for a product or service. This research aims to find out what strategies BSI KC Padangsidimpuan implements in marketing Hasanah Card products. Through a marketing strategy analysis approach, this research tries to identify the factors that influence the marketing success of Hasanah Card and formulate strategic recommendations that can increase the marketing effectiveness of the product. This research uses qualitative methods while the data collection methods used are interviews, observation and documentation. The results of this research show that the Hasanah Card marketing strategy carried out by BSI KC Padangsidimpuan uses a marketing mix system which is usually called product, price, place, promotion.